Employment relations in the informal sector: A need for redefinition - Hasbullah, N.; Dzurizah Ibrahim (Conscientia Beam, 2020)
The International Labor Organization (ILO) in the 'Report of the Committee on Employment Relationship' states that current employment relationships are increasingly complex and there is no acceptable definition to define 'employment relationships'. Thus, this paper aims to investigate whether employment relations exist in the informal sector. By using Goss’ framework, this can be understood by two related dimensions. First, the extent to which employers are dependent on his or her employees, and vice versa, and second, the extent to which employees have the capacity, individually or collectively, to challenge the power of their employer. Based on these two dimensions, four distinct categories have been identified that reveal the complexity and diversity of the nature of employment relationships in the informal sector: fraternalism, paternalism, benevolent autocracy, and passive acquiescence. In-depth interviews with four employers and four workers in the informal sector in Lawas, Malaysia were conducted. The findings indicate that the nature of employment relations in the informal sector is benevolent autocracy as employers are less dependent on their employees, resulting in limited labor capacity to challenge the employer's power. A characteristic of the informal sector (such as a family-based business and not legally registered) is the lack of protection for workers, which is the main reason for shaping employment relations in this sector. It is recommended, therefore, to have policy reforms to protect the rights of workers in the informal sector